Delayed treatment seeking and its associated factors among people with schizophrenia spectrum disorders who are on follow-up at Dilla University Referral Hospital in the southern region of Ethiopia, 2022: a cross-sectional study - Negash, Misrak; Temesgen, Bethel; Kassaw, Chalachew; Abebe, Lulu; Moges, Solomon; Sime, Yohanes; Yimer, Solomon (Frontiers in Psychiatry, 2023)
Background: Delay in psychiatric treatment leads to increased morbidity and mortality, as well as the emergence of several psychiatric and physical comorbidities and the use of life-threatening and life-altering self-treatments (such as licit and illicit substance misuse). Delay detection and taking preventive measures against its modifiable factors are crucial for a better prognosis.Objective: To assess delayed treatment seeking and its associated factors among people with schizophrenia spectrum disorders who are on follow-up at Dilla University referral hospital in Southern region, Ethiopia.Method: An institution-based cross-sectional study was conducted from June 8-September 11, at Dilla University referral hospital in Southern region, Ethiopia, 2022. Epicollect was used to collect data from 414 randomly selected participants using an interviewer-administered questionnaire.Delayed treatment seeking was determined using participants' medical records and a semistructured questionnaire. Data were analyzed using Statistical Package for Social Sciences (SPSS) version 26. Logistic regression analysis was done to identify the explanatory variables of delayed treatment.The magnitude of delayed treatment seeking was 49.8% (95%CI=44.9, 54.3). Study participants with disengaged family cohesion (AOR=3.97, 95%CI = (2.999, 7.193), inflexible family adaptability (AOR=2.00, 95%CI= (1.686, 4.044), who lack awareness about the availability of psychiatric treatment(AOR=1.63, 95%CI=(1.362, 2.626), high internalized stigma(AOR=3.24, 95%CI=(2.770, 5.514), and those with a negative attitude toward psychiatric treatment(AOR=2.88, 95%CI=(2.034, 4.469) had delayed treatment seeking. Whereas participants whose educational status was higher than diploma (AOR=0.040, 95%CI= (0.026, 0.077) and high school (AOR=0.09, 95%CI= (0.071, 0.204) were less likely to have delayed treatment seeking.There is a significant delay in seeking modern psychiatric treatment. Stigma, lack of awareness about where treatment is available, disengaged family cohesion, inflexible family adaptability, and distance to health facility higher than 5km, and negative attitude toward psychiatric treatment were barriers to seeking appropriate care.